Efektivitas Terapi Non-Farmakologi Pada Pasien Hipertensi - Nadiya Widda Mawaddah; Damayanti, Ervina; Pardilawati, Citra Yuliyanda (Medula, 2024)
Hypertensive disease is the leading cause of early death worldwide. Hypertension is a common chronic medical condition characterized by sustained increases in arterial pressure. The high risk of side effects in the use of antihypertensive medicine for a long period of time causes non-pharmacological therapy of hypertension to be an alternative choice. This study aims to determine the effectiveness of non-pharmacological therapy in hypertensive patients in reducing and controlling normal blood pressure. The study used a literature review method with data sources of international scientific journals and articles using the PubMed database. The information search strategy used a combination of keywords such as "non-pharmacological therapy for hypertension" and "the effectiveness of non-pharmacological therapy in hypertension". Through the database search, 190 scientific articles and journals were obtained. A total of 12 scientific journals and articles were selected as reference sources for research that met the criteria. The results obtained from 12 journals and scientific articles showed that non-pharmacological therapy for hypertension was effective in reducing systolic and diastolic blood pressure. Non-pharmacological therapies recommended according to the reference sources are lifestyle modification, increasing physical activity such as aerobic exercise, intake of low sodium salt, acupuncture therapy, listening to music, relaxation therapy and increasing compliance with therapeutic interventions.